PESAN MORAL DALAM KUMPULAN CERPEN SENYUM KARYAMIN KARYA AHMAD TOHARI - Fairuz Hanisworo, Luthfi; Maharani Umaya, Nazla; Ngatmini, Ngatmini (Universitas Islam Sumatera Utara, 2023)
This study aims to describe the form of the moral message in Ahmad Tohari's collection of short stories Senyum Karyamin and describe the way of delivery in the short story collection of Smile Karyamin by Ahmad Tohari. The method used in this research is descriptive qualitative method. Collecting data in this study using reading and note techniques. The results of this study indicate a form of moral message, namely hard work, loyal friends, tolerance, mutual help, mutual respect, don't be arrogant, responsibility, self-introspection, patience, and honesty. The results of further research, namely the way of conveying moral messages are divided into two, namely directly and indirectly. Direct delivery can be seen through monologues and dialogues, while indirect delivery can be seen through the context of events.